Embracing resilience in multiple sclerosis: a new perspective from COVID-19 pandemic. Issue 2 (7th February 2022) - Sbragia, Elvira; Colombo, Eleonora; Pollio, Chiara; Cellerino, Maria; Lapucci, Caterina; Inglese, Matilde; Mancardi, Gianluigi; Boffa, Giacomo
ABSTRACT: Coronavirus disease 2019 (COVID-19) resulted in several psychological consequences. Past epidemiological experiences already showed the deep albeit heterogeneous psychological repercussions of pandemics. Nevertheless, little is known about COVID-19 outbreak and the possible strategies for boosting resilience in patients with chronic diseases such as Multiple Sclerosis (MS). Therefore, we designed a study aiming to assess the changes in mental distress during COVID-19 outbreak in patients with MS and to identifyfactors contributing to resilience's development. We enrolled 106 patients (69 relapsing-remitting, 20 secondary-progressive, and 17 primary-progressive) whose neuropsychological assessment before the COVID-19 pandemic (1 January 2019–1 March 2020) was available. It consisted of Brief International Cognitive Assessment for MS (BICAMS), Hospital Anxiety and Depression Scale (HADS) and patient-reported MS Neuropsychological Screening Questionnaire (MSNQ-P). All patients were re-tested during Italian lockdown through an online survey, comprehensive of sociodemographic information, HADS self-rating Scale, MSNQ-P Questionnaire and finally Connor-Davidson Resilience self-rating Scale (CD-RISC 25), in order to evaluate resilience. No significant changes in HADS and MSNQ-P scores were detected during COVID-19 pandemic in our population. Though, pre-existing lower HADS and MSNQ-P scores but not demographic, disease- and treatment-related elements were found significantly (p < 0.0001) and independently associated with a better resilience attitude.